Exploring the role and mechanisms of MAGEA4 in tumorigenesis, regulation, and immunotherapy - Weijian Zhu; Qiang Yi; Zheng Chen; Jiaqi Wang; Kui Zhong; Xinting Ouyang; Kuan Yang; Bowei Jiang; Jianing Zhong; Jinghua Zhong (Molecular Medicine)
Abstract MAGEA4 is a member of the Melanoma-Associated Antigen (MAGE) family, characterized by high expression in various tumor tissues but low expression in normal tissues, with the exception of testis and placenta. Its expression is associated with poor prognosis in cancer. This review summarizes the mechanisms of action, regulatory functions, and immunotherapeutic applications of MAGEA4 in cancer.MAGEA4 promotes tumor initiation and progression through multiple pathways, including ubiquitination and degradation of the tumor suppressor P53, regulation of cell cycle and apoptosis, modulation of DNA damage repair, and enhancement of cancer cell survival. By forming a complex with TRIM28, MAGEA4 accelerates tumor development via P53 degradation. Factors such as TWIST1 and BORIS can upregulate MAGEA4 expression. MAGEA4 interacts with proteins including Miz-1, p53, and RAD18, participating in gene transcription regulation and DNA damage repair. By stabilizing RAD18, MAGEA4 facilitates the recruitment of Y-family DNA polymerases, enabling cells to continue replication under DNA damage conditions and thus supporting cancer cell survival. MAGEA4-based TCR-T cell therapy and cancer vaccines show clinical potential. This article comprehensively reviews the structure and function of MAGEA4, as well as recent research progress in solid tumors, providing a theoretical foundation for the clinical translation of MAGEA4 and its application in immunotherapy.